2021
DOI: 10.3390/nu13041082
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19-Related Lockdown on Diet and Serum Markers in Healthy Adults

Abstract: Due to limited data about the impact of lockdown on health status, the present study aimed to investigate the impact of COVID-19-related lockdown on changes in dietary habits, physical activity and serum markers in healthy adults. A total of 38 asymptomatic adults aged from 23 to 59 with a normal BMI (22.5 kg/m2) participated in baseline and post-lockdown measurements that included dietary and physical activity assessment, anthropometric measurements and blood samples; and the lockdown survey which included di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 56 publications
(79 reference statements)
2
33
0
2
Order By: Relevance
“…Modification of lifestyle by COVID‐19 lockdown caused also perceived stress, 33 worse sleep quality, 33,34 reduced physical activity 29,34‐36 and altered dietary habits (ie variable adherence to Mediterranean diet, 29,33,37 lower meat and fish consumption, 29 high fast food consumption 29 and reduced consumption of fresh food 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Modification of lifestyle by COVID‐19 lockdown caused also perceived stress, 33 worse sleep quality, 33,34 reduced physical activity 29,34‐36 and altered dietary habits (ie variable adherence to Mediterranean diet, 29,33,37 lower meat and fish consumption, 29 high fast food consumption 29 and reduced consumption of fresh food 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the total HEI scores in the present study were much lower than a 2019 study of U.S. college students at a state university, who reported a mean total HEI score of 63.3 [ 44 ]. A limited number of studies have quantitatively assessed HEI during the COVID-19 pandemic [ 16 , 31 ]. In a sample of adults in Quebec, Canada, LaMarche et al [ 16 ] observed a small increase in 2015-HEI scores (+1.1 points) during the early COVID-19 lockdown relative to the prepandemic baseline (mean: 69.0 points).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have evaluated the impact of the early COVID-19 pandemic on dietary quality or other aspects of dietary intake [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. The majority of studies reported lower dietary quality [ 9 , 11 , 14 , 15 , 19 , 20 , 21 , 22 , 29 , 30 , 31 ], with one study showing improved overall HEI [ 16 ] and others indicating improved dietary quality in some aspects [ 20 , 21 , 24 , 27 ], such as increased intake of fruits and vegetables [ 27 ] and decreased intake of alcoholic beverages [ 20 , 24 , 27 ] and sugar-sweetened beverages [ 21 ]. Four of the aforementioned studies evaluated the effect of the pandemic on dietary intake among college students, including one in Vietnam [ 15 ], one in Italy [ 13 ], one in Spain [ 27 ], and one multi-country study, which included a small sample from the U.S. […”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Bogataj Jontez, et al in healthy individuals [ 31 ], there was also a slight worsening in diet quality during quarantine; however, concerning dietary intake of vitamin D, it remained considerably below the RDA’s during five months of quarantine. Although in our study, dietary intake assessment was only performed once, as previously reported in a population-based study by Ramírez-Silva, et al [ 12 ], the dietary intake of vitamin D in the Mexican population is 2.62 ± 1.22 μg; therefore, according to this report, vitamin D intake was estimated to be deficient in the patients evaluated regardless of pandemic containment measures.…”
Section: Discussionmentioning
confidence: 99%